Human Factors and Peri-operative Safety: Compliance with Five Steps to Safer Surgery (5STSS) Protocols at an NHS Hospital during the SARS-CoV2 Pandemic1 - Human Factors Implications - Dr Asekhame Oise Isemede; Dr Sarah O. Beckley (International Journal of Innovative Research in Medical Science, 2021)
The five steps to safer surgery processes are essential standards for the delivery of safe surgery. The steps are Team Brief, World Health Organization (WHO) - Sign In, Time Out, Sign Out and Team Debrief. With increased anxieties and other disruptive human factors associated with the COVID-19 pandemic capable of negatively affecting care standards, this audit of compliance with the five steps to safer surgery was done to determine if peri-operative safety standards have been maintained or not during the COVID-19 pandemic1 at the Trust. Methods: A retrospective audit of completeness of documentations of the above five steps (used as proxy for compliance) obtained from electronic medical records of a sample of patients who had surgical procedures during the COVID-19 pandemic1 (Part A) and a survey of peri-operative staff on COVID-19 and peri-operative care (Part B) were carried out after approval by the audit department of the Trust. Results: Compliance with Team Briefs, WHO - Sign In, Time Out and Sign Out were comparable to 2019 audit and national standards but there was a fall in compliance with Team Debrief from 100% (pre-COVID-19 audit) to 52%. Fear of getting infected with COVID-19 and lack of suitable care guidelines were found to be potent anxiety factors for the majority of respondents, all the respondents supported a review of the current peri-operative care pathway. Conclusion: All causes including human factors contributing directly or indirectly to the fall in standards seen in this audit need to be explored and strategies (solutions) such as development of new peri-operative care pathways capable of improving team resilience for more effective and safer peri-operative care should be urgently considered.